Barriers in physical access to maternal health services in rural Ethiopia - Okwaraji, Yemisrach B. (BMC Health Serv Res, 2015)
BACKGROUND: Identifying women with poor access to health services may inform strategies for improving maternal and child health outcomes. The aim of this study was to explore risk factors associated with access to health facilities (in terms of physical distance) among women of reproductive age (15–49 years) in Dabat district, a rural area of north-western Ethiopia. METHODS: A randomly selected cross sectional survey of 1,456 rural households was conducted. Data were collected during home visits. Data on household assets and socio-demographic data (including age, education level, occupation, religion and ethnicity) were collected on 1,420 women. A geographic information system (GIS) was used to map locations of all households, the district health centre and the smaller health posts. Travel time from households to health facilities was estimated, incorporating information on the topography and terrain of the area. The primary outcomes were: 1) travel time from household to nearest health post 2) travel time from household to health centre. Analysis was conducted using multiple linear regression models and likelihood ratio tests. RESULTS: This study found evidence that educated women lived closer to health centres than uneducated women (adjusted mean difference (adj MD) travel time −41 min (95 % CI: −50,–31)) in this community. Woman’s age was also associated with distance to the health centre. Women aged 15–20 years were more likely to live in a poor access area compared with women aged 21–30 years (adj MD travel time −11 min (95 % CI: −23, 0)), and with women aged 31–49 years (adj MD travel time −32 min (95 % CI: −47,-17)). There was no evidence to suggest that travel time to the health centre was associated with household wealth. CONCLUSIONS: Our main aim was to address the almost total lack of research evidence on what socio-demographic characteristics of women of reproductive age influence access to health facilities (in terms of physical distance). We have done so by reporting that our study found an association that women with no education and women who are younger live, on average, further away from a health facility in this rural Ethiopian community. While we have generated this valuable information to those who are responsible for providing maternal and child health services locally, to fully understand access in health care and to promote equitable access to health care, our study could thus be extended to other components of access and explore how our findings fit into the wider context of other factors influencing maternal health outcomes and utilisation of maternal health services such as antenatal care or delivery at health facility.